PEMANFAATAN LIMBAH ELEKTRODA AKI PADA PROSES ELEKTRODEKOLORISASI LARUTAN ZAT WARNA - Apipah, Lutfia (Chem Info Journal, 2013)
Industrial waste had caused some reduction of water quality, one of them is liquid waste of coloring or dyeing batik production which contains indigosol dye and remazol black B that being dumped to water directly while the environment has limited capability to degradate that dye. Electrolysis method had been chosen as one alternative to cope with dye waste, because its benefits compare to other methods which are effective and simple. One of supporting factor of this method is the electrode being used. This research is destined to decolorized indigosol and remazol black B dye, using PbO2/Pb from used battery as electrode and reducing Chemical Oxygen Demand (COD) number. This research using PbO2/Pb as electrode obtained from battery electrodes waste. This method electrolyze dye sample on 8 volt using PbO2/Pb electrode obtained from used battery and conducted in 150 minutes. Final result of the electrolysis will be qualitatively and quantitavely analyze using UV-VIS spectrophotometer, and analyze Chemical Oxygen Demand (COD). The research result indicated that the use of PbO2/Pb electrode from used battery can reduce color intensity, respectively by 98.02% and 99.42% each for indigosol and remazol black B dye, and could reduce COD number respectively to 28.47% and 51.47% for each dye.